Conquering the pink invader: a triumph over Roseomonas mucosa bacteraemia in an elderly patient - Zainulabid, Ummu Afeera; Maharon, Nor Adila; Ismail, Ismaliza; Chee, Loon Leong (Elsevier, 2024)
Roseomonas mucosa, a distinctive Gram-negative bacterium characterized by its pink segmented coccoid rod morphology, belongs to a genus initially misclassified as Methylobacterium. First identified in 1993 by Rihs et al., Roseomonas has since been classified into four subspecies: R. gilardii, R. cervicalis, R. mucosa, and R. fauriae. This microorganism is naturally found in water and soil, raising concerns about potential modes of transmission, such as through contaminated water sources like faucets. While Roseomonas infections are relatively rare, they have been documented in various clinical settings, including bloodstream infections, cerebrospinal fluid, skin, and soft tissues. Despite its infrequency, the pathogen's clinical significance is underscored by its ability to cause infections in individuals with underlying health conditions.